Cannabinoids in Gynecological Diseases - Petra Luschnig; Rudolf Schicho (Medical Cannabis and Cannabinoids)
The endocannabinoid system (ECS) is a multifunctional homeostatic system involved in many physiological and pathological conditions. The ligands of the ECS are the endocannabinoids, whose actions are mimicked by exogenous cannabinoids, such as phytocannabinoids and synthetic cannabinoids. Responses to the ligands of the ECS are mediated by numerous receptors like the classical cannabinoid receptors (CB1 and CB2) as well as ECS-related receptors, e.g., G protein-coupled receptors 18 and 55 (GPR18 and GPR55), transient receptor potential ion channels, and nuclear peroxisome proliferator-activated receptors. The ECS regulates almost all levels of female reproduction, starting with oocyte production through to parturition. Dysregulation of the ECS is associated with the development of gynecological disorders from fertility disorders to cancer. Cannabinoids that act at the ECS as specific agonists or antagonists may potentially influence dysregulation and, therefore, represent new therapeutic options for the therapy of gynecological disorders.